2018
DOI: 10.1007/s10614-018-9803-z
|View full text |Cite
|
Sign up to set email alerts
|

Human and Machine Learning

Abstract: In this paper, we consider learning by human beings and machines in the light of Herbert Simon's pioneering contributions to the theory of Human Problem Solving. Using board games of perfect information as a paradigm, we explore differences in human and machine learning in complex strategic environments. In doing so, we contrast theories of learning in classical game theory with computational game theory proposed by Simon. Among theories that invoke computation, we make a further distinction between computable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…The form of transfer learning demonstrated by our dynamic architecture-acquiring new knowledge (new expert) based on indirect knowledge of what other parts of the network (old experts) know-has not been reported before to our knowledge. This form of transfer learning is reminiscent of "learning by analogy," a learning skill humans are very good at, but machines continue to struggle with [31], [32]. Through our framework, this dynamic form of transfer could be extended to much larger networks, utilizing a myriad of experts.…”
Section: Discussionmentioning
confidence: 99%
“…The form of transfer learning demonstrated by our dynamic architecture-acquiring new knowledge (new expert) based on indirect knowledge of what other parts of the network (old experts) know-has not been reported before to our knowledge. This form of transfer learning is reminiscent of "learning by analogy," a learning skill humans are very good at, but machines continue to struggle with [31], [32]. Through our framework, this dynamic form of transfer could be extended to much larger networks, utilizing a myriad of experts.…”
Section: Discussionmentioning
confidence: 99%
“…Neuron is actually a mathematical model constructed by simulating biological neurons [13]. Its function is similar to biological neurons.…”
Section: Machine Learning Theorymentioning
confidence: 99%
“…The model shows great advantages in decision validation and data availability [ 12 ]. Kao and Venkatachalam studied the relationship among business model, big data, and enterprise innovation performance and found that big data technology can be employed as a driving force for enterprise innovation and development [ 13 ].…”
Section: Review and Analysis Of Related Researchmentioning
confidence: 99%